The Dynamics of Evangelism in a Multicultural Context: Challenges and Opportunities for Contextualization - Soegianto Soegianto; Prinsipessia Putri Abigail Lolong (Jurnal Didaskalia, 2023)
Evangelism in a multicultural context has become a primary concern in the mission of the modern church. In an effort to comprehend the dynamics involved in evangelism within multicultural environments, this research aims to identify the primary challenges faced by evangelists while also detailing the emerging opportunities in the endeavor to contextualize the message of the Gospel. Through an in-depth literature review in qualitative research, this study reveals the complexity of the multicultural context within the scope of evangelism. The main challenges encompass differences in religious beliefs, language disparities, and cultural tensions, all of which necessitate a prudent and adaptable approach. However, within these challenges, significant opportunities also arise. These opportunities include the formation of intercultural bridges, an improved understanding of religious pluralism, and the potential for collaboration among people of different faiths. The research findings emphasize the importance of contextualizing the Gospel message to establish an effective and meaningful approach within a multicultural context. This study provides valuable insights for churches and evangelists operating in multicultural environments, stimulating discussions about the role of contextualization in disseminating the message of the Gospel in an increasingly diverse society.